THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, WORK ENVIRONMENT, AND COMPENSATION ON THE WORK LOYALTY OF UNIVERSITY OF MUHAMMADIYAH JEMBER EMPLOYEES - Afifa, Hani Nur; Trias Setyowati; Septi Holisa Umamy (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research is based on the existence of problems at the University of Muhammadiyah Jember, namely the transformational leadership style which includes charisma, inspiration, intellectual stimulation, and also individual attention. The second problem is the Work Environment, which includes the work atmosphere, relationships with colleagues, and the availability of work facilities. The third problem is Compensation, which includes salary, incentives, allowances, and facilities. These factors have a great influence on increasing the work loyalty of employees, so it is necessary to conduct a study. Method: The data used in this study are primary data and secondary data. The population and sample consist of employees of the University of Muhammadiyah Jember, with a total of 130 employees. The sampling technique used in this study is Proportional Stratified Sampling, while data analysis is conducted using multiple linear regression analysis. Results: Based on the results of the study, it can be concluded that the variables of transformational leadership style, work environment, and compensation partially have a significant positive effect on employee loyalty at the University of Muhammadiyah Jember. Novelty: This study highlights the significant positive influence of transformational leadership style, work environment, and compensation on employee loyalty at the University of Muhammadiyah Jember. The findings emphasize the importance of leadership practices that foster motivation and concern for employees, the need for an inclusive and well-equipped work environment, and the role of fair and transparent compensation in enhancing employee loyalty.